Impact of change in iron status over time on clinical outcomes in heart failure according to ejection fraction phenotype. (30th September 2021) - Fitzsimons, Sarah; Yeo, Tee Joo; Ling, Lieng H.; Sim, David; Leong, Kui Toh Gerard; Yeo, Poh Shuan Daniel; Ong, Hean Yee; Jaufeerally, Fazlur; Ng, Tze P.; Poppe, Katrina; Lund, Mayanna; Devlin, Gerry; et al.
Abstract: Aims: The importance of iron deficiency (ID) in heart failure with preserved ejection fraction (HFpEF) is unknown. In HF with reduced ejection fraction (HFrEF), ID is reported as an independent predictor of mortality in HF although not all published studies agree. Different definitions of ID have been assessed, and the natural history of untreated ID not established, which may explain the conflicting results. This study aimed to assess the relationship between ID and mortality in HFpEF, clarify which definition of ID correlates best with outcomes in HFrEF, and determine the prognostic importance of change in ID status over time. Methods and results: Analyses were conducted on data from 1563 patients participating in a prospective international cohort study comparing HFpEF with HFrEF. Plasma samples from baseline and 6 month visits were analysed for the presence of ID. Two ID definitions were evaluated: IDFerritin = 'ferritin < 100 mcg/L or ferritin 100–300 mcg/L + transferrin saturation < 20%' and IDTsat = 'transferrin saturation < 20%'. The risk of all‐cause mortality and death/HF hospitalization associated with baseline ID (IDFerritin or IDTsat ) and change in ID status at 6 months (persistent, resolving, developing, or never present) was estimated in multivariable Cox proportional hazards models. Of 1563 patients, 1115 (71%) had HFrEF and 448 (29%) HFpEF. Prevalence of ID was similar in HFpEF and HFrEF (58%). Patients with ID were more likely to be female, diabetic, and have a higher co‐morbid burden than patients without ID. ID by either definition did not confer independent risk for either all‐cause mortality or death/HF hospitalization for patients with HFpEF [IDFerritin hazard ratio (HR) 0.65 (95% confidence interval 0.40–1.05), P = 0.08; IDTsat HR 1.16 (0.72–1.87), P = 0.55]. In the overall study cohort (HFrEF + HFpEF) and HFrEF subgroup, IDFerritin was inferior to IDTsat in prediction of all‐cause mortality [overall cohort: HR 1.21 (0.95–1.53), P = 0.12 vs. HR 1.95 (1.52–2.51), P < 0.01; HFrEF: HR 1.12 (0.85–1.48), P = 0.43 vs. HR 1.57 (1.15–2.14), P < 0.01]. Persistence of IDTsat at 6 months was strongly associated with poor outcomes compared with never having IDTsat [HR 2.22 (1.42–3.46), P < 0.01] or having IDTsat at baseline self‐resolve by 6 months [HR 1.40 (1.06–1.86), P = 0.02]. Conclusions: Iron deficiency is equally prevalent in HFpEF and HFrEF but is negatively prognostic only in HFrEF. The natural history of ID is important; persistent ID is strongly associated with mortality whereas resolution is not. IDTsat is the superior definition of ID and should inform future trials investigating the efficacy of intravenous iron replacement in patients with HFrEF.